2010
DOI: 10.2165/11319740-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Match and Training Injuries in Rugby League

Abstract: Rugby league is an international collision sport played by junior, amateur, semiprofessional and professional players. The game requires participants to be involved in physically demanding activities such as running, tackling, passing and sprinting, and musculoskeletal injuries are common. A review of injuries in junior and senior rugby league players published in Sports Medicine in 2004 reported that injuries to the head and neck and muscular injuries were common in senior rugby league players, while fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 61 publications
4
58
0
3
Order By: Relevance
“…Five review studies [3,9,14,20,21] were included in the data collection but were not utilised for the pooled analysis. The studies selected for inclusion reported rugby league match [7,13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (n = 19) and training [7,13,[39][40][41][42] (n = 6) concussion injuries within their datasets (see Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Five review studies [3,9,14,20,21] were included in the data collection but were not utilised for the pooled analysis. The studies selected for inclusion reported rugby league match [7,13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (n = 19) and training [7,13,[39][40][41][42] (n = 6) concussion injuries within their datasets (see Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been nine key findings from these previous studies [9,10,13]. (1) There was no difference between injury rates for first and reserve grade players [9]; (2) there were significant differences between injury rates for different sites of the body, with the lower limbs having the highest injury rate [9]; (3) there was a small but not significant risk of injury when playing as a forward compared with playing as a back [9]; (4) more concussions were recorded in amateur than professional (risk ratio [RR] 2.4 [95 % confidence interval (CI) 1.5-3.8]; p = 0.0002), semi-professional (RR 3.0 [95 % CI 1.8-5.1]; p \ 0.0001) and junior (RR 2.5 [95 % CI 1.2-5.5]; p = 0.0132) studies [10]; (v) the lower limb was the most common injury recorded (5.7 [95 % CI 5.1-5.8] per 1000 training hours) for all studies reporting training sessions [10]; (6) there were more concussions recorded in semi-professional than amateur (RR 13.5 [95 % CI 4.2-43.9]; p \ 0.0001) training session studies [10]; (7) the non-time-loss (NTL) match injury rate was 5.6 (95 % CI 5.0-6.4) times higher than the time-loss (TL) injury rate [13]; (8) lacerations to the head and neck accounted for 77 % (95 % CI 70-83) of all NTL lacerations [13]; and (9) NTL concussions accounted for 71 % (95 % CI 58-80) of all concussions [13].…”
mentioning
confidence: 94%
“…AlĂ©m do rĂșgbi caracterizar-se como um esporte de contato e de muita exigĂȘncia fĂ­sica, os movimentos especĂ­ficos como maul, ruck, scrum (formação ordenada) e tackle (placagem) aumentam significativamente o risco de lesĂ”es musculoesquelĂ©ticas durante os treinamentos e jogos [1][2][3][4][5][6][7][8]. Apesar das lesĂ”es na regiĂŁo da cabeça e dos membros inferiores ainda serem as mais comumente reportadas, alguns estudos tĂȘm relatado um aumento na frequĂȘncia de lesĂ”es na articulação do ombro, tanto em atletas profissionais como amadores [4,[9][10][11][12].…”
Section: Introductionunclassified
“…A revisĂŁo de literatura de King et al [2] demonstrou que o complexo articular do ombro Ă© responsĂĄvel por 28% das lesĂ”es musculoesquelĂ©ticas do rĂșgbi, enquanto a recente revisĂŁo de Kaux et al [3] apresentou uma percentagem menor (6,5%) de lesĂ”es nessa regiĂŁo. Em outra recente revisĂŁo de literatura, Papalia et al [13] descrevem que as lesĂ”es no complexo articular do ombro estĂŁo relacionadas a severos danos aos tecidos moles que envolvem especificamente essa articulação, tambĂ©m denominada de glenoumeral.…”
Section: Introductionunclassified
“…Of particular interest has been research into injury incidence in different settings and at different levels of performance (e.g. Hodgson et al [1]; Gabbett [2]; Gabbett [3]; King et al [4]). …”
Section: Introductionmentioning
confidence: 99%